Shastriji Maharaj - Dave, Kiśora Ma. (Kiśora Mahipatarāma), 1936- (Text book of Satsang educational series, 1977)
On the life and teachings of Swami Yajñapurushadāsa, 1863-1949, religious leader of the Svāmīnārāyaṇa sect of Hinduism.